The jumping spider genus Thiodina Simon, 1900 reinterpreted, and revalidation of Colonus F.O.P-Cambridge, 1901 and Nilakantha Peckham & Peckham, 1901 (Araneae: Salticidae: Amycoida) - Bustamante, Abel A.; Maddison, Wayne P.; Ruiz, Gustavo R.s. (Zootaxa, 2015)
In this paper we call attention to the identity of the type species of Thiodina Simon, 1900, T. nicoleti Roewer, 1951. When Simon proposed the genus, he characterized it based on morphological features found in species he described, but not found in the type species he designated, and whose type specimens, apparently, he had not examined. Nicolet’s original description makes it clear that the type species is not closely related to the more familiar species placed in the genus. This misinterpretation was followed by contemporary researchers and survives until today. Here we designate and describe a neotype for T. nicoleti. We revalidate Colonus F.O.P.-Cambridge, 1901 and Nilakantha Peckham & Peckham, 1901 to transfer most species formerly placed in Thiodina. The combinations Colonus puerperus (Hentz, 1846), Nilakantha cockerelli Peckham & Peckham, 1901 and N. peckhami Bryant, 1940 are restored. The following new combinations are established: Colonus branicki (Taczanowski, 1871) new comb., C. candidus (Mello-Leitão, 1922) new comb., C. germaini (Simon, 1900) new comb., C. hesperus (Richman & Vetter, 2004) new comb., C. melanogaster (Mello-Leitão, 1917) new comb., C. pallidus (C.L. Koch, 1846) new comb., C. pseustes (Chamberlin & Ivie, 1936) new comb., C. punctulatus (Mello-Leitão, 1917) new comb., C. rishwani (Makhan, 2006) new comb., C. robustus (Mello-Leitão, 1945) new comb., C. sylvanus (Hentz, 1846) new comb., C. vaccula (Simon, 1900) new comb., C. vellardi (Soares & Camargo, 1948) new comb., Nilakantha beugelorum (Wolff, 1990) new comb., N. crucifera (F.O.P.-Cambridge, 1901) new comb., and N. inerma (Bryant, 1940) new comb. Thiodina setosa Mello-Leitão, 1947 is tentatively transferred to Cotinusa Simon, 1900.